The impact of college students’ physical exercise on negative emotion: The chain mediating role of self-efficacy and smartphone addiction - Rui Li; Hao-yu Li; Hao-jie Zuo; Jia-meng Sun; Qi Liu; Chen-Xi Li; Ning Zhou; Bo Li; Mohamad Nizam Nazarudin (PLoS ONE, 2026)
Objective Against the backdrop of widespread smartphone adoption, rising student stress levels, and the increasing prevalence of negative emotions, this study employs a chain-mediation model to investigate the relationship between physical exercise and negative emotions among university students. It further elucidates the mediating roles of self-efficacy and smartphone addiction in this association. Methods Data from the 2022 China Physical Activity and Health Longitudinal Survey (CPAHLS-CS) were used, involving a sample of 16,355 college students from East China and Central China. Measurements were taken using the Physical Activity Rating Scale (PARS-3), the Depression, Anxiety, and Stress Scale (DASS-21), the Physical Activity Self-Efficacy Scale (PASS), and the Mobile Phone Addiction Tendency Scale (MPATS). Descriptive analysis, correlation analysis, regression analysis, and chain mediation effect testing were performed using SPSS 27.0, Excel, and the PROCESS plugin, controlling for confounding variables such as gender, grade, region, and age. Results The study found a significant negative correlation between physical exercise and negative emotions in university students (r = −0.564, p < 0.001). Self-efficacy and smartphone addiction both played significant mediating roles in the relationship between physical exercise and negative emotion. The mediation effects included independent mediation by self-efficacy and smartphone addiction, as well as a chain mediation effect between the two, with effect sizes of 0.005 and −0.017, respectively. Conclusion This study offers a novel theoretical perspective on the relationship between physical exercise and negative emotions, elucidating the associations among physical exercise, self-efficacy, smartphone addiction, and negative emotions. The findings suggest that physical exercise may regulate negative emotions by enhancing self-efficacy and mitigating smartphone addiction, thereby providing empirical support for mental health intervention practices within the university student population.